2015
DOI: 10.1097/iae.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Optical Density Analysis of Subretinal Fluid After Surgical Repair of Rhegmatogenous Retinal Detachment

Abstract: Changes in optical density ratios of the residual SRF after retinal detachment repair may be representative of changes in the SRF composition over time. This is in agreement with previous biochemical studies and may serve as a noninvasive method of assessing SRF content in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…We demonstrated that reflectivity ratios can be used as diagnostic markers to differentiate between retinal pathologies. Kashani et al 24 used the same method to investigate changes in the OD of the SRF after RRD repair. They found that ODR measurements increase significantly over time after surgery, and might reflect an increased concentration of photoreceptor OS fragments in the SRF as the serous component is absorbed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that reflectivity ratios can be used as diagnostic markers to differentiate between retinal pathologies. Kashani et al 24 used the same method to investigate changes in the OD of the SRF after RRD repair. They found that ODR measurements increase significantly over time after surgery, and might reflect an increased concentration of photoreceptor OS fragments in the SRF as the serous component is absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the SRF after surgical repair of RRD did not find ODR to be a significant predictor of visual acuity. 24 To the best of our knowledge, and based on a careful search of PubMed.com (1988-2014, [in the public domain] http://www.ncbi.nlm.nih.gov/pubmed), this appears to be the first study to describe the relationship between preoperative measurement of ODR in RRD and visual outcome. As discussed above, OD is influenced by changes in fluid composition.…”
Section: Discussionmentioning
confidence: 99%
“…14 In another study, optical density ratios from OCT scans were used as a surrogate measure of SRF composition Table 3 Final visual acuities, foveola ellipsoid zone (EZ), and external limiting membrane (ELM) scores for patients in whom PSF was found on OCT and subsequently absorbed (resolved PSF group), compared with patients in whom subfoveolar fluid was not found on the first post-operative OCT scan (non-PSF group) following surgery. 16 This ratio increased in conjunction with a decrease in height of subretinal fluid and was suggested to reflect an increasing particulate concentration of subretinal fluid during the process of subretinal fluid absorption. 16 Retinal detachments secondary to atrophic holes and dialyses are not dependent upon development of a PVD.…”
Section: Discussionmentioning
confidence: 99%
“…16 This ratio increased in conjunction with a decrease in height of subretinal fluid and was suggested to reflect an increasing particulate concentration of subretinal fluid during the process of subretinal fluid absorption. 16 Retinal detachments secondary to atrophic holes and dialyses are not dependent upon development of a PVD. 17 They frequently present when acute symptomatic progression of a chronic asymptomatic peripheral detachment occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The application of SD-OCT, FAF, mfERG, and microperimetry are a major step forward in this direction but it is likely that additional tests of RPE health will be necessary to understand the biochemical and pharmacologic function of the cells after transplantation. For example, quantitative FAF, 22 in vivo, real-time spectroscopy, 109,110 and a host of SD-OCT-based measures of tissue composition [111][112][113] present promising technology that can resolve cellular and molecular changes in retinal tissue. 114 Identification and quantification of outcome parameters in cell-based therapies will also be challenging.…”
Section: Considerations For Surgical Implantationmentioning
confidence: 99%